CONSTRUCTING THE POLLUTION PROBLEM: MEDIA FRAMES AND PUBLIC PERCEPTION OF ENVIRONMENTAL CRISES (Contemporary Journal of Social Science Review, 2025)
Pollution is a critical global challenge threatening environmental sustainability, public health, and social justice, yet public understanding of pollution is shaped more by media representation than firsthand experience. This study examines how traditional and digital media construct the pollution problem through narrative framing and how these frames influence public perception, emotion, and responsibility. Using a qualitative research design, the study analyzed 350 media texts, including news reports, social media posts, and environmental campaign material, and conducted 20 semi-structured interviews to explore audience interpretation. The results identify five dominant framing strategies: scientific and technical framing, human-interest and emotional narratives, political and economic conflict framing, responsibility framing, and environmental-justice framing. Findings show that scientific frames establish legitimacy but lack emotional resonance, while human-interest narratives generate empathy and engagement. Political and responsibility frames produce ideological polarization and shift accountability toward individuals rather than structural actors. Environmental-justice frames, though less frequent, strongly shape moral urgency and highlight inequalities. The research demonstrates that emotional storytelling influences public trust and motivates environmental action, whereas politicized framing fosters confusion and disengagement. The study concludes that the media do not merely report pollution but construct its meaning through symbolic power, shaping whether pollution is perceived as an inevitable cost of progress or a solvable injustice requiring collective action. Effective environmental communication must integrate scientific clarity with emotional and ethical resonance to mobilize public support and advance policy reform.